Makroekonomiczne uwarunkowania handlu towarami rolno-spożywczymi w Polsce - Kułyk, Piotr (Macroeconomic Determinants of Polish Agro-Food Trade, 2006)
The carried out analysis reveals that there were significant changes in Polish agro-food trade from 1993 to 2004. At the beginning of this period Poland was a net exporter and a the end it became a structural importer. The changes were determined by macroeconomic factors. Especially the agriculture support policy was one of the most important determinants of Polish agro-food trade. In the long term gross domestic product has the great importance too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 514-519